Conduct books and the history of the ideal woman - Kenlon, Tabitha (Anthem Press, 2020)
"Conduct Books and the History of the Ideal Woman" examines six centuries of conduct manuals and other instructive writing, analyzing the history of gendered expectations that have been debated in print from the fourteenth century and continue to influence our present thinking about women's roles and abilities.